Similarities of the K/Pc dinoflagellate cyst associations between South Atlantic and Indian proto-oceans - De Menezes, Jï¿½nior Bispo; Garcia, Maria Judite; Premaor, Eduardo; De Oliveira, Paulo Eduardo; Arai, Mitsuru [UNESP]; Bernardes-De-Oliveira, Mary Elizabeth Cerruti; Kavali, Pauline Sabina; Shivanna, Mahesh (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
In this contribution we present the composition of the Late Cretaceous / Paleocene dinoflagellate cyst assemblages found in the Pelotas Basin, southern Brazil in order to provide a first paleobiogeographical comparison between this location, India and other former Gondwana continents: South America (Argentina and Uruguay), Africa (Nigeria and Western Ghana), Antarctica, Australia, and New Zealand. A total of 13 taxa, some endemic and other cosmopolitan were identified. The paleoenvironment of the Gondwana former members basins, as previously presented and attested by the dinoflagellate cysts are marginal marine nearshore, varying from neritic to shallow neritic and lagoonal or coastal swamps, which permitted the deposition of sediments in anoxic marine conditions. The present analysis of similarity between K/Pc dinoflagellate cyst associations allowed the establishment of paleobiogeographic distribution.
Keywords: Cretaceous; Dinoflagellate cysts; Gondwanan paleobiogeographic distribution; Paleocene